Aspirin, but Not Tirofiban Displays Protective Effects in Endotoxin Induced Lung Injury. - Jessica Tilgner; Klaus Thilo von Trotha; Alexander Gombert; Michael J Jacobs; Maik Drechsler; Yvonne Döring; Oliver Soehnlein; Jochen Grommes (PLoS ONE, 2016)
BACKGROUND:Treatment of acute lung injury (ALI) remains an unsolved problem in intensive care medicine. Recruitment of neutrophils into the lungs, regarded as a key mechanism in progression of ALI, depends on signaling between neutrophils and platelets. Consequently we explored the effect of platelet-targeted aspirin and tirofiban treatment in endotoxin induced acute lung injury. METHODS:C57Bl/6 mice were exposed to aerosolized LPS (500μg/ml) for 30min and treated with Aspirin (100μg/g bodyweight via intraperitoneal injection, 30 min before or 1 hour after LPS inhalation) or Tirofiban (0.5μg/ g bodyweight via tail vein injection 30 min before or 1 hour after LPS inhalation). The count of alveolar, interstitial, and intravascular neutrophils was assessed 4h later by flow cytometry. Lung permeability changes were assessed by FITC-dextran clearance and protein content in the BAL fluid. RESULTS:Aspirin both before and after LPS inhalation reduced neutrophil influx into the lung and lung permeability indicating the protective role of Aspirin in ALI. Tirofiban, however, did not alter neutrophil recruitment after LPS inhalation. Release of platelet-derived chemokines CCL5 and PF4 and neutrophil extracellular traps was reduced by Aspirin but not by Tirofiban. CONCLUSION:Aspirin, but not Tirofiban reduces neutrophil recruitment and displays protective effects during endotoxin induced lung injury.